Synthesis and analysis of request signals optimal detector in aircraft responders of secondary ob-servation systems - Обод, І.І.; Свид, І.В.; Штих, І.А. (Radiotekhnika, 2017)
The structure of the detector optimized for the Neumann - Pearson criterion of the request signals in aircraft transponders with several antenna systems for receiving secondary airspace surveillance systems was synthesized and the analysis of the detection quality was carried out. It was shown that implementation of joint processing of the request signals of all spatially separated channels of the aircraft transponder resulted in an improvement in the quality of the request signals detection.